DIGITAL TECHNOLOGIES IN THE SYSTEM OF LABOR EDUCATION OF CHILDREN WITH HEARING IMPAIRMENTS - Bekmanova, Jamilya Abdullayevna; Jabbarbergenov, Shinbergen Embergenovich (SCIENCE and SOCIETY, 2026)
The article examines the possibilities and prospects of using digital technologies in the system of labor education for children with hearing impairments. Modern approaches to the use of information and communication technologies, multimedia tools, and specialized software in the educational process are analyzed. Special attention is paid to adapting digital tools to the specific educational needs of children with sensory impairments. Practical recommendations are presented for implementing digital technologies in labor education, aimed at increasing the effectiveness of professional competence formation and the social adaptation of students with hearing impairments.